Pengembangan Aplikasi Ajukan Instan (AJUKIN) Sebagai Solusi Digital Dalam Mendukung Pengajuan Surat Di SMPN 2 Jember - Nisa, Vadilatun (Pakis Journal Institute, 2024)
This research aims to develop an online application called AJUKIN (Ajukan Instan) designed to simplify the letter submission process at SMP Negeri 2 Jember. Traditional manual methods for letter submission have proven inefficient, leading to delays and increased workload for administrative staff. The AJUKIN application utilises a Google-based framework that integrates google sites, google forms, google sheets, and autocrat to facilitate quick and efficient submission of letters from students. This research utilises a Research and Development (R&D) methodology using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which allows for systematic needs analysis, structured application design, and iterative evaluation based on feedback from users. The app allows students to submit their requests digitally, thus improving the overall efficiency of the service. Testing and evaluation involving students and administrative staff showed that AJUKIN has fulfilled most of the expected functions, providing significant benefits in terms of efficiency and accessibility. However, further development is needed to enhance the application's capabilities and adapt it for wider use in educational environments.